The flexible working hours framework strategy adopted by the Global Banking Sector during Covid-19 pandemic Era - Davidzo Hope Mapuvire; Victor Kudakwashe Mapuvire (Indiana Publications, 2023)
The impact of Covid-19 on workers and workplaces across the globe has been substantial. Covid-19 has become both a global health crisis as well as an international economic threat. The lockdown measures introduced as an attempt at curbing the spread of the virus have had a broad range of unique and fundamental challenges for both employers as well as employees across the globe. Whilst the Covid-19 pandemic abruptly put to an end the normal working routines, it also resulted in the acceleration of trends which were already taking place such as the migration of work to online or virtual environments as well as flexible working hours where employees were not required to be physically present at the workplace. As a result, the year 2020 has brought unprecedented changes to the global economy and the world of work. This paper attempts an evaluation of the flexible working hours framework strategy adopted by the global banking sector during covid-19 pandemic era. The article relied upon a qualitative case study approach in which data was obtained through secondary data which was collected through the review of literature from books, journals, publications and newspaper articles. Finding’s reveal that, even though flexible working hours have allowed employees to work from is a system that has not been without its faults, as there have been some challenges that have been noted. In addition, there have been numerous effects of the flexible working hours framework strategy adopted players in the financial services sector covid-19 pandemic. This paper therefore recommends that, in order to minimise the impact of the Covid-19 pandemic on the banking sector, there is need to ensure that, there is full digitalisation of operations, improved communication, workforce training as well as conditions that promote work-Life Balance.